Survival in nunatak and peripheral glacial refugia of three alpine plant species is partly predicted by altitudinal segregation - Francesco Rota; Pau Carnicero; Gabriele Casazza; Juri Nascimbene; Peter Schönswetter; Camilla Wellstein (Molecular Ecology, 2024)
Mountain biota survived the Quaternary cold stages most probably in peripheral refugia and/or ice‐free peaks within ice‐sheets (nunataks). While survival in peripheral refugia has been broadly demonstrated, evidence for nunatak refugia is still scarce. We generated RADseq data from three mountain plant species occurring at different elevations in the southeastern European Alps to investigate the role of different glacial refugia during the Last Glacial Maximum (LGM). We tested the following hypotheses. (i) The deep Piave Valley forms the deepest genetic split in the species distributed across it, delimiting two peripheral refugia. (ii) The montane to alpine species Campanula morettiana and Primula tyrolensis survived the LGM in peripheral refugia, while high‐alpine to subnival Saxifraga facchinii likely survived in several nunatak refugia. (iii) The lower elevation species suffered a strong population decline during the LGM. By contrast, the higher elevation species shows long‐term stability of population sizes due to survival on permanently ice‐free peaks and small population sizes at present. We found peripheral refugia on both sides of the Piave Valley, which acted as a major genetic barrier. Demographic modelling confirmed nunatak survival not only for S. facchinii but also for montane to alpine C. morettiana . Altitudinal segregation influenced the species' demographic fluctuations, with the lower elevation species showing a significant population increase at the end of the LGM, and the higher elevation species either showing decrease towards the present or stable population sizes with a short bottleneck. Our results highlight the role of nunatak survival and species ecology in the demographic history of mountain species.